2018
DOI: 10.1111/jen.12559
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Bemisia tabaci MEAM1 and Trialeurodes vaporariorum on Tomato chlorosis virus (ToCV) infected plants

Abstract: Whiteflies are important agricultural pests of several crops and cause great economic losses, mainly by the transmission of plant viruses. Among the different species of whiteflies, Trialeurodes vaporariorum and Bemisia tabaci MEAM1 (B biotype) transmit the crinivirus Tomato chlorosis virus (ToCV). Previous studies report that virus‐infected plants can influence the attractiveness and the behaviour of different species of whiteflies. In this study, we evaluated the number of eggs, egg hatching rate and emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…This results can explain why B. tabaci MED has replaced MEAM1 in the past decade in China. However, ToCV infection did not influence the number of eggs laid by Trialeurodes vaporariorum [ 16 , 34 , 35 ]. Previous research confirmed the B. tabaci MED fecundity affected by the semi-persistent virus, ToCV [ 16 , 36 , 37 ], which is consistent with our observation.…”
Section: Discussionmentioning
confidence: 99%
“…This results can explain why B. tabaci MED has replaced MEAM1 in the past decade in China. However, ToCV infection did not influence the number of eggs laid by Trialeurodes vaporariorum [ 16 , 34 , 35 ]. Previous research confirmed the B. tabaci MED fecundity affected by the semi-persistent virus, ToCV [ 16 , 36 , 37 ], which is consistent with our observation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, according to Shi et al (), B. tabaci MED adults performed better on infected plants while according to Li et al (), they performed worst. On the other hand, B. tabaci MEAM1 adults performed similarly on infected and healthy plants according to Shi et al () and Maluta et al (), while they performed worst on infected plants according to Watanabe et al (). Although the effects of plant pathogens on the behaviour and biological performance of their vectors have been shown for different host–pathogen–vector combinations, from the available studies carried out with ToCV it is clear that additional research is needed to correctly understand the interactions between the virus, the plant host and whiteflies, and their further epidemiological implications.…”
Section: Epidemiologymentioning
confidence: 81%
“…Additionally, nonviruliferous MED preferred to settle on ToCV‐infected plants and viruliferous MED preferred to settle on healthy ones, contributing to the virus spreading (Shi et al , ). A study from Brazil showed that ToCV is harmful for MEAM1, and dramatically decreases its adult emergence and survival rates (Watanabe et al , ). These results help to explain the interaction between whiteflies and plants infected with viruses, in which each whitefly species has different behaviour according to the virus and host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Weed plants can thus easily serve as alternative hosts for several begomoviruses in the absence of tomato crops, and can also contribute to begomovirus variability, as the same plant can be infected by several virus species, contributing to the occurrence of recombination and rearrangements (García‐Arenal and Zerbini, ). Moreover, the performance of whiteflies can be improved on virus‐infected plants, with increased reproduction and survival rates, which can lead to faster and more efficient virus spread (Chen et al , ; Shrestha et al , ; Watanabe et al , ).…”
Section: Introductionmentioning
confidence: 99%